The translation technique analysis of assertive speech acts in Venom movie subtitles - Devy Sagitasari (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2022)
The objective of this study is to find out the translation techniques in assertive speech acts of Venom movie subtitles by professional and amateur translators. The researchers used the qualitative method in analyzing the selected assertive speech acts data which are taken from the script and classifying them according to Searle (1969) theory, then classify the translation techniques according to Molina and Albir (2002) theory. The findings showed there are 144 utterances (data) of assertive speech acts. The total of single assertive speech acts is 136 (0.9%) utterances, the total of couplet assertive speech acts is 7 (0.06%) utterances, the total of single translation technique by the professional translator is 36 (0.39%) utterances, the total of single translation techniques by the amateur translator is 65 (0.43%) utterances, the total of couplet translation technique by the professional translator is 62 (0.44%) utterances, the total of duplet translation technique by the amateur translator is 56 (0.41%) utterances, the total of triplet translation techniques by the professional translator is 23 (0.21%) utterances, the total of triplet translation techniques by the amateur translator is 19 (0.18%) utterances, the total of quadruplet translation techniques by the professional translator is 3 (0.03%) utterances, the total of quadruplet translation techniques by the amateur translator is 3 (0.03%) utterances. Hopefully, this research is helpful for the future researcher, especially those who deal with the translating skill Keywords: Translation; Translation techniques; Assertive speech acts; Subtitle